A hypervelocity star with a Magellanic origin - Erkal, D; Boubert, D; Gualandris, A; Evans, N; Antonini, F (Oxford University Press, 2018)
Using proper motion measurements from Gaia Data Release 2, we probe the origin of 26 previously known hypervelocity stars (HVSs) around the Milky Way. We find that a significant fraction of these stars have a high probability of originating in the Milky Way Galaxy, but there is one obvious outlier. HVS3 is highly likely to be coming almost from the centre of the Large Magellanic Cloud (LMC). During its closest approach, 21.1+6.1−4.6 Myr ago, it had a relative velocity of 870+69−66 km s−1 with respect to the LMC. This large kick velocity is only consistent with the Hills mechanism, requiring a massive black hole near the centre of the LMC. This provides strong evidence that the LMC harbours a massive black hole of at least 4×103--104M⊙⁠.